CAN THE APPLICATION OF AGROFORESTRY AT MONOCULTURAL FOOD CROP AREAS SUPPORT MANUFACTURER CHEMICAL FERTILIZER REDUCTION PROGRAMS WITHOUT SACRIFICING FARMERS' INCOME? - Bakri, Samsul; Suripto Dwi Yuwono,; Rahayu Sulistiowati,; Sri Septyastuti,; Ida Nurhaida,; Nanda Kurniasari, (The American Journal of Social Science and Education Innovations, 2024)
In an agroforestry system, nutrients from the subsoil can be made available to food plants through the absorption process by trees with deep roots. However, shade from canopy tree plants can suppress photosynthesis and reduce food crop production and farmer income [INCM]. This antagonism needs to be evaluated when introducing agroforestry programs into monoculture food crop areas to reduce manufactured chemical fertilizers application. This research was carried out from June to August 2023 at Natar District, South Lampung Regency to determine the effect of tree strata (teak, acacia, and albizia), multi-proposed tree species or MPTS (Parkia speciosa, avocado, and jack fruit), shrubs (coffee and cacao), and ground cover (vegetables, peanut, and soybean) to [INCM]. Interviewing forty respondents who were still retaining one or more of these tree strata among food crops including upland rice, corn, and cassava. The OLS (ordinary least square) model was employed at 90% confidence level. To eliminate the model error, the variables ownership of productive assets (upland, cattle, sheep, and cock), fertilizer application (urea, ponska, KCl and liquid fertilizer), compost, and pesticide use were also incorporated in the model. The results suggest the significant effects: (1) that positive ones are acacia, teak, vegetables, peanuts, and, soybeans, respectively USD 86.4 (P=0.000); 88.3 (P=0.000); 109,5 (P=0.000); 114.6 (P =0.000); 145.1 (P=0.000); and (2) which negative were Albizia falcataria, Parkia speciosa, avocado, coffee, and cacao respectively of around USD 31,7 (P=0.002); 57.1 (P=0.000); 43.2 (P=0.003); 62,0 (P=0.000) and 96.37 (P=0.000).